HIV-1 genetic diversity and compartmentalization in mother/infant pairs infected with CRF01_AE - Tovanabutra S. (2014)
Molecular characterization of C2-V5 envelope sequences from maternal plasma, peripheral blood mononuclear cells (PBMC), cervical secretions and infant PBMC was performed in eight CRF01_AE-infected mother/infant pairs. Maternal viruses were relatively homogeneous within a compartment but distinct in different compartments in mothers with high CD4 cell counts. Infant viruses were almost distinct, but phylogenetically related, to maternal viruses, mostly from the maternal PBMC compartment, reflecting the frequent transmission of HIV-1 from maternal cells rather than free viruses. © 2007 Lippincott Williams & Wilkins, Inc.